Corncob residue as heterogeneous acid catalyst for green synthesis of biodiesel: A short review - Mardina, Primata; Wijayanti, Hesti; Tuhuloula, Abubakar; Hijriyati, Erita; Sarifah (Communications in Science and Technology, 2021)
The utilization of an appropriate catalyst in biodiesel production depends on the free fatty acid content of vegetable oil as a feedstock. Recently, heterogeneous acid catalysts are widely chosen for biodiesel production. However, these catalysts are non-renewable, highly expensive and low stability. Due to the aforementioned drawbacks of commercial heterogeneous acid catalyst, a number of efforts have been made to develop renewable green solid acid catalysts derived from biomass. Published literature revealed that the application of the biomass derived solid acid catalysts can achieve up to 98% yield of biodiesel. This article focused on corncob as raw material in solid acid catalyst preparation for biodiesel production. The efficient preparation method and performance comparation are discussed here. The corncob derived heterogeneous acid catalysts provides an environmentally friendly and green synthesis for biodiesel production.